2003
DOI: 10.3989/scimar.2003.67n4451
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite variation in the Mexican rockfish <i>Sebastes macdonaldi</i>

Abstract: SUMMARY: The Mexican rockfish Sebastes macdonaldi is the Northeast Pacific rockfish with the southernmost distribution, featuring isolated populations in the Gulf of California. We analysed seven microsatellite loci in 111 organisms collected throughout most of its geographical range to test long-standing hypotheses regarding its disjunct distribution. One locus was fixed and the number of alleles in polymorphic loci ranged from 2 to 24 (average 13.5). We found very high levels of polymorphism (overall He = 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…We found no differentiation among wild S. inermis populations, despite different sea basin origins. The lack of significant genetic differentiation between the wild populations we sampled is consistent with the lack of genetic divergence found in wild S. inermis from mtDNA sequence variability studies (Higuchi and Kato, 2002), as well as that of other Sebastes species (Rocha-Olivares et al, 2003;Gilbert-Horvath et al, 2006). This could result from sufficient gene flow during the black rockfish pelagic phase.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…We found no differentiation among wild S. inermis populations, despite different sea basin origins. The lack of significant genetic differentiation between the wild populations we sampled is consistent with the lack of genetic divergence found in wild S. inermis from mtDNA sequence variability studies (Higuchi and Kato, 2002), as well as that of other Sebastes species (Rocha-Olivares et al, 2003;Gilbert-Horvath et al, 2006). This could result from sufficient gene flow during the black rockfish pelagic phase.…”
Section: Discussionsupporting
confidence: 67%
“…In this study, the genetic variation of wild population samples of Korean S. inermis was low relative to that reported in other Sebastes species (Rocha-Olivares et al, 2003;Buonaccorsi et al, 2002Buonaccorsi et al, , 2004, as well as other marine fishery species (DeWoody and Avise, 2000). However, similar genetic variability was reported in S. maliger (Wimberger et al, 1999) and S. thompsoni (Sekino et al, 2001).…”
Section: Discussionmentioning
confidence: 67%
“…2003). For example, Sebastes macdonaldi , the Mexican rockfish, is the southernmost species of the northeast Pacific rockfishes (Rocha‐Olivares et al . 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Marine species generally possess significantly higher levels of genetic diversity (average H e = 0.79) than freshwater (average H e = 0.46) or anadromous (average H e = 0.68) species (DeWoody and Avise 2000). For example, other studies using microsatellite markers have demonstrated expected heterozygosities of 72–75% and averages of 17.3, 11.8, and 13.5 alleles per locus for Sebastes rastrelliger (six loci) (Buonaccorsi et al 2004), Sebastes caurinus (nine loci) (Buonaccorsi et al 2002), and Sebastes macdonaldi (seven loci) (Rocha‐Olivares et al 2003), respectively. Eight microsatellite loci described for four North Atlantic redfish ( Sebastes fasciatus , Sebastes mentella , Sebastes marinus , and Sebastes viviparus ) were also highly polymorphic (0.5 ≤ H e ≤ 0.96) and at least half the loci had H e > 0.8 in all species (Roques et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Mexican rockfish, the southernmost of the northeastern Pacific rockfishes, also shows no evidence of genetic differentiation. Despite reasonable levels of polymorphism, population samples from throughout the Mexican rockfish's range were not distinct when analyzed using both mtDNA sequence information (Bernardi et al 2003) and seven microsatellite loci (Rocha‐Olivares et al 2003). With 16 microsatellite loci, kelp rockfish ( Sebastes atrovirens ) specimens collected from an 800‐km stretch along the central California coastline exhibited apparent genetic homogeneity (Gilbert‐Horvath et al 2006).…”
Section: Discussionmentioning
confidence: 99%